The acute effect of aerobic and resistance training on arterial diameter: A meta-analysis - Briceño Torres, José Miguel (2017)
Purpose: The purpose of the study was to investigate the acute response of two exercise modes (aerobic and resistance training) on the endothelium vascular diameter. Methods: A meta-analysis was planned where the inclusion criteria for studies were: 1) experimental trials; 2) only one exercise session (acute treatment); 3) aerobic (AE) or resistance training (RT) interventions; 4) studies in human adults with no heart disease; 5) studies published only in English language; and 6) studies with pre and post flow-mediated dilation (FMD) measurement. The electronic search was performed in six databases (PubMed, Springer Link, Science Direct, SAGE Journals, Sport Discus and Nature), cross-referencing, and hand searching, using the following combinations of words “Acute exercise FMD”, “endothelial exercise function”, “vascular exercise endothelium”, and “FMD exercise”. Hedge’s standardized mean difference effect size (ES) was calculated for each result; then, ESs pooled using random-effects models. Non-overlapping 95% confidence intervals (CI95%) were considered statistically significant. Heterogeneity was assessed using Q and I2, while funnel plots and Egger’s regression test were used to assess small-study effects (potential bias). Results: A total of 13 studies were meta-analyzed and 40 ESs computed from 378 (245 men and 133 women) participants. Of the 40 ESs, 27 were on AE, 9 on RT and 4 on control groups (no exercise). The AE training revealed no significant effect on artery diameter (ES= 0.26; CI95%= 0.00, 0.52; Q= 14.2; p= 0.11; I2= 0%). The RT interventions indicated no significant effect (ES= 0.29; CI95%= -0.08, 0.66; Q 0.38; p= 0.25; I2= 0%). Conclusions: Neither aerobic or resistance training elicited an acute response on vascular function. More research is needed to better understand the physiological mechanisms responsible for this response.